Density of mucosal mast cells in the lamina propria of the colon and terminal ileum of children. Issue 7 (July 1985) - Sanderson, I R; Slavin, G; Walker-Smith, J A
Abstract : Ileal and colonic biopsies from children observed to be histologically normal were fixed in Carnoy's fluid, sectioned, and stained by the chloroacetate esterase reaction. The density of mucosal mast cells was higher in the terminal ileum than the colon, but did not vary significantly within the colon.